Hodgkin Lymphoma A Comprehensive Update on Diagnostics and Clinics - Engert, Andreas; Horning, Sandra J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This book provides a well-illustrated, comprehensive, and up-to-date account of Hodgkin lymphoma. Epidemiology, pathogenesis, and the role of the microenvironment are examined in detail. The initial clinical evaluation and use of staging systems are fully discussed, and prognostic factors are carefully considered. The various treatment options for first-line and relapsed Hodgkin lymphoma are presented, including the newly available treatments for recurrent disease and the management required in special clinical circumstances. Given the very high cure rates and the young age of many patients, there is an increasing need to develop better individually tailored treatment strategies that will help to avoid both early and late side-effects of treatment. Such strategies receive due attention, and clear guidance is provided on the handling of Hodgkin survivors. This book will be of great value to hematologists, oncologists, and all others with an interest in Hodgkin lymphoma.
Part I: From Hodgkin's Disease to Hodgkin Lymphoma -- The History of Hodgkin Lymphoma.-Epidemiology.-The Role of Viruses in the Genesis of HL.-Pathology and Molecular Pathology of Hodgkin Lymphoma.-Microenvironment and Immune Escape Mechanisms -- Part II: Diagnosis and Treatment -- Clinical evaluation.-Functional Imaging.-Prognostic Factors.-Principles of Radiation Techniques in Hodgkin Lymphoma.-Principles of Chemotherapy in Hodgkin Lymphoma.-Treatment of Early Favorable Hodgkin Lymphoma.-Treatment of Early Unfavorable Hodgkin Lymphoma.-Treatment of Advanced-Stage Hodgkin Lymphoma.-ReLapsed and Refractory Hodgkin lymphoma.-Pediatric Hodgin Lymphoma -- Part III: Special Clinical Situations Lymphocyte-predominant Hodgkin lymphoma.-The Managment of Hodgkin Lymphoma during Pregnancy.-The Management of HIV-Hodgkin Lymphoma.-The Management of Elderly Patients with Hodgkin Lymphoma.-Allogeneic Stem Cell Transplant in Hodgkin Lymphoma.-New Drugs. Part IV: Survivorship -- Survivorship in Hodgkin Lymhoma.-Second Neoplasias.-Cardiovascular and Pulmonary Late Effects.-Gonadal Dysfunction and Fertility Preservation. Part V: Future Prospects- What will we learn from Genomics and Proteomics?-The Future: Personalized Medicine in Hodgkin Lymphoma.
Keywords: Medicine; Hematology; Oncology; Medicine & Public Health; Hematology; Oncology